Reconstruction of impacts on a composite plate using fiber Bragg gratings (FBG) and inverse methods. (1st August 2016) - Rezayat, A.; De Pauw, B.; Lamberti, A.; El-Kafafy, M.; Nassiri, V.; Ertveldt, J.; Arroud, G.; Vanlanduit, S.; Guillaume, P.
Abstract: Composite materials are nowadays widely used in several applications, especially in the aerospace field. Despite the numerous advantages that composites can offer, the health monitoring of this type of structures is challenging. A major challenge regards the detection and monitoring of delaminations. In the case of aeronautical structures, delaminations are often caused by impacts with external objects. Therefore, the capability of detection, localization and reconstruction of occurring impacts becomes an essential health monitoring tool for the estimation of the remaining structure lifetime. In this paper, we propose a new procedure for the reconstruction of impacts, based on the structural model and on measured vibration data. The procedure is tested over a carbon fiber reinforced composite plate, instrumented with surface mounted fiber Bragg grating sensors. The experimental results show that the proposed algorithm (VS-LS) can localize and reconstruct the impact forces with at least three times better accuracy than the classical pseudo-inverse method.